Is it possible to calculate surface areas of intraoral structures from preoperative CT scan?. Issue 8 (August 2017) - Ramella, Vittorio; Bottosso, Stefano; Franchi, Alberto; Papa, Giovanni; Bussani, Rossana; Arnež, Zoran Marji
Summary: Microsurgical reconstruction of intraoral structures requires accurate planning of flap shape and dimensions. The goal of this study is to describe a method that allows to calculate surfaces of oral structures from preoperative CT-scan in order to determine a precise flap design before the surgery. We created casts of the human mouth from cadavers with a head and neck CT-scan available using an impression material. We digitalized the mouth casts and unwrapped the surfaces of the different structures of the mouth in a bi-dimensional plane in order to measure the area. Furthermore, we measured distances from pre-determined bony landmarks using the CT-scan 3D reconstruction model and we correlated the two type of measurements. We performed a simple regression analysis and afterwards a multivariate analysis using the more statistically correlated measurements. We found a statistical correlation between the surface of the tongue and the surface floor of the mouth with three bone distances that let us to create three mathematical formulas. With those formulas, we can calculate the surfaces of the tongue and the floor of the mouth using simple bony distances that can be easily measured from the head and neck preoperative CT scan. Using standard template's layouts, we can create a precise preoperative flap design in the reconstruction of the tongue and of the floor of the mouth.